Regulation of Th1/Th2 and Th17/Treg by pDC/mDC imbalance in primary immune thrombocytopenia. Issue 15 (August 2021) - Li, Qinzhi; Liu, Yang; Wang, Xiujuan; Sun, Mingling; Wang, Lei; Wang, Xinyou; Liu, Ying; Fan, Wenxia; Zhang, Kaile; Sui, Xiao; Guo, Xinhong
This study investigates the regulatory effect of plasmacytoid dendritic cells (pDC)/myeloid dendritic cells (mDC) imbalance on balance of Th1/Th2 and Th17/Treg in primary immune thrombocytopenia (ITP). A total of 30 untreated ITP patients and 20 healthy controls were recruited. Compared with healthy control, the pDC proportion of ITP patients was significantly reduced ( P  = 0.004), while the mDC proportion was not significantly changed ( P  = 0.681), resulting in a decrease in the pDC/mDC ratio ( P  = 0.001). Additionally, compared with controls, serum levels of interleukin (IL)-6, IL-12, and IL-23 were increased in ITP patients ( P  < 0.001), and mRNA levels of IL-12p40, IL-12p35, and IL-23p19 were also increased ( P =0.014, P  = 0.043, P  < 0.001). Compared with the healthy control, the proportion of Th1 and Th17 cells in ITP patients increased ( P  = 0.001, P  = 0.031). Serum levels of interferon gamma (IFN-γ) and IL-17 in ITP patients also increased ( P  = 0.025, P  = 0.005). Furthermore, T-bet and RORγt mRNA levels were increased in peripheral blood of ITP patients ( P  = 0.018, P  < 0.001). Correspondingly, the proportion of Th2 and Treg cells decreased ( P  = 0.007, P  < 0.001), along with a decrease in serum IL-4 and transforming growth factor beta (TGF-β) ( P  = 0.028, P  = 0.042), and an increase in GATA-3 mRNA ( P  < 0.001). However, there was no significant difference in Foxp3 mRNA levels ( P  = 0.587). Pearson correlation analysis showed that the proportion of total dendritic cells (DCs) was positively correlated with IL-12 ( r  = 0.526, P  = 0.003) and IL-23 ( r  = 0.501, P  = 0.005) in ITP patients. Th1/Th2 ratio, IFN-γ, and IL-12 levels were negatively correlated with platelet counts ( r  = −0.494, P  = 0.009; r  = –0.415, P  = 0.028; r  = –0.492, P  = 0.032). However, IL-23 was positively correlated with IL-17 ( r  = 0.489, P  = 0.006) and negatively correlated with platelet count ( r  = –0.564, P  = 0.001). The ratio of IL-6 and Th17 cells was negatively correlated with platelet count ( r  = –0.443, P  = 0.014; r  = –0.471, P  = 0.011). The imbalance of pDC/mDC and the increase of IL-6, IL-12, and IL-23 lead to the increased differentiation of CD4+ T cells into Th1 and Th17 cells, which might be the important mechanisms underlying the imbalance of Th1/Th2 and Th17/Treg in ITP patients.